2007
DOI: 10.1152/ajplung.00075.2007
|View full text |Cite
|
Sign up to set email alerts
|

The role of the receptor for advanced glycation end-products in lung fibrosis

Abstract: The pathogenesis of pulmonary fibrosis remains unclear. The receptor for advanced glycation end-products (RAGE) is a multi-ligand receptor known to be involved in the process of fibrotic change in several organs, such as peritoneal fibrosis and kidney fibrosis. The aim of this study was to examine the contribution of RAGE during the acute inflammation and chronic fibrotic phases of lung injury induced by intratracheal instillation of bleomycin in mice. Bleomycin-induced lung fibrosis was evaluated in wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 46 publications
(49 reference statements)
4
110
2
Order By: Relevance
“…A separate study showed the significant down-regulation of RAGE in lung homogenates and ATII cells from patients with IPF, as well as in bleomycin-treated mice (Queisser et al, 2008). These findings conflict with results from previous papers showing that RAGE contributes to bleomycin-induced lung fibrosis (He at al., 2007;Hamada et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A separate study showed the significant down-regulation of RAGE in lung homogenates and ATII cells from patients with IPF, as well as in bleomycin-treated mice (Queisser et al, 2008). These findings conflict with results from previous papers showing that RAGE contributes to bleomycin-induced lung fibrosis (He at al., 2007;Hamada et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…RAGE also contributes to bleomycin-induced lung fibrosis (He et al, 2007;Hamada et al, 2008). RAGE over-expression is evident in areas of active fibrosis, including fibroblastic foci (Morbini et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with other reports in which inhibition of the interaction of RAGE with its ligands led to a reduced inflammation in models of hepatic injury (19 -21), diabetic atherosclerosis (22, 23), delayed-type hypersensitivity (24, 25), type II collagen-induced arthritis (25), and sepsis (24). In addition, in a recent study, RAGE was found to be important for the development of lung fibrosis upon intratracheal administration of bleomycin (42). Because activation of RAGE triggers multiple intracellular signaling pathways, including NF-B, resulting in the transcription of proinflammatory factors (43,44), these findings could at least in part be attributed to the blockade of RAGE interaction with its ligands via diminished activation of NF-B, resulting in attenuated tissue injury/damage and/or inflammation (24,45).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies revealed that RAGE expression produces paradoxical responses in different models of pulmonary fibrosis (33)(34)(35). The effect of hyperoxia on RAGE expression has been shown to differ between adult mouse and neonatal rat models (12,13).…”
Section: Discussionmentioning
confidence: 99%